Photothermal controls of vegetative dormancy in Poa secunda. Issue 1 (30th April 2022) - Chen, Allen A.; Fei, Shui‐zhang; Lenssen, Andrew W.; Moore, Kenneth J.
Abstract: Background: Summer vegetative dormancy is a desirable trait in cool‐season grasses when they are interplanted with annual crops. Sandberg bluegrass ( Poa secunda J. Presl.) shows summer dormancy, but the environmental cues that control dormancy remain unknown. Methods: A controlled environment study using temperature and day length combinations of 32.2°C/15 h, 26.6°C/14 h, 21.1°C/13 h, and 15.5°C/12 h was conducted with P. secunda accessions PI232347, PI639272, and PI232348, and 'Audubon' red fescue as a nondormant control to determine the optimum treatment for dormancy induction. A second study using treatments of 26.6°C/14 h, 21.1°C/13 h, and 15.5°C/12 h was conducted to determine the thresholds for dormancy release. A third study used a factorial experiment with two temperatures (32.2°C and 15.5°C) and two day lengths (15 and 12 h) to differentiate between temperature and day length effects on dormancy induction. Results: Of the four temperature and day length combinations, all except for 15.5°C/12 h resulted in dormancy by the end of 6 weeks, with 32.2°C/15 h inducing dormancy in only 17 days. Of the three treatments for dormancy release, 15.5°C/12 h broke dormancy the fastest in all accessions and released the most number of plants from dormancy. Considerable variation existed between accessions for the speed of dormancy release in the 21.1°C/13 h and 26.6°C/14 h treatments. The third study showed that temperature is the primary inducer for summer dormancy, while longer day length may promote dormancy under inductive temperatures. Conclusions: This study identified the optimum photothermal for induction and release of summer dormancy in P. secunda, which will help future studies in elucidating the mechanism of summer dormancy. Abstract : Summer dormant cool‐season grasses are ideal as perennial groundcovers for row crops to provide ecological services as they likely pose less competition to the main crop. This study identified environment conditions that control summer dormancy induction and release in the summer dormant Poa secunda (top) and nondormant creeping red fescue (bottom).